Memaksimalkan Kinerja Karyawan Melalui Peningkatan Employee Engagement dan Budaya Organisasi - Sukma Dewi, Ni luh putu Nopinda; Agustina, Made Dian Putri; Kusyana, Dewa Nyoman Benni (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
Employee performance is the performance of employees both in quantitative and qualitative units which will greatly determine the survival of a company. Every company needs to encourage employee engagement with work and also improve organizational culture so that individual employee performance can increase. This study aims to determine the effect of employee engagement and organizational culture on employee performance. This research was conducted at PT. Agung Jaya Internasional Badung, Bali Province with a population of 32 employees. This study uses census techniques so that all members of the population are involved as research subjects. Primary data collection was carried out using questionnaires and interviews. The measurement scale uses a Likert scale which consists of five answer choices. Hypothesis testing is done using multiple linear regression. Based on the results of the analysis, it can be concluded that (1) employee engagement has a positive and significant effect on employee performance, (2) organizational culture has a positive and insignificant effect on employee performance.